GE_GERICHTE A/640/2021 vom 4. Oktober 2021 - GE Cour de justice (2021)
TAXATION CONSÉCUTIVE À UNE PROCÉDURE;SOUSTRACTION D'IMPÔT;DROIT PÉNAL FISCAL | LIFD.151.al1; LIPP.59.al1; LIFD.175.al1; LPFisc.69.al1